Impacts of field margin orientation on populations of soil‐dwelling invertebrates in relation to the direction and intensity of field traffic. (5th November 2021) - Carlesso, Léa; Beadle, Andrew; Cook, Samantha M.; Hartwell, Graham; Mead, Andrew; Ritz, Karl; Sparkes, Debbie; Wu, Lianhai; Murray, Phil J.
Abstract: Sown field margins are a central part of agri‐environmental schemes aiming to improve biodiversity and ecosystem services in agricultural landscapes. Despite the knowledge that key services are delivered by belowground biodiversity, the impacts of field margins on populations of soil invertebrates both within the margins and the neighbouring crops remain unclear. We investigated the effect of field margin orientation with respect to the direction of the tramlines upon populations of soil‐dwelling mesofauna with focus on Acari (mites) and Collembola (springtails). Two margins on adjacent sides of the same field and their neighbouring cropped areas were examined: one margin oriented perpendicular to the tramlines, and one parallel to the tramlines. This sampling design was repeated on two farms with distinct soil management (no till vs. minimum tillage) and crop rotation (diverse‐long‐rotation vs. cereal/oilseed‐short‐rotation) in two seasons (autumn vs. spring) over two years. The distribution of invertebrates in the cropped areas depended on the orientation of the margins and the taxa studied. Reduced abundance of Collembola and Acari were found at both farms in the cropped area where machinery turns (margin perpendicular to tramlines), in comparison with the cropped area where margins and tramlines were parallel. This study suggests the existence of interacting impacts between the margins and field operations (trafficking and resulting compaction) on populations of soil mesofauna.